Technology dissemination and extension services activated by department of fisheries in south west region of Bangladesh - Rahman, BMS; Samad, MA; Khanom, M; Raseduzzaman, M (Journal of the Bangladesh Agricultural University, 2011)
The study was conducted in Khulna, Satkhira and Jhenaidah districts under Khulna division. The purpose was to know the training of fishery officers, fish and shrimp farmers in aqua farming. The main dissemination processes are training of farmers, farm demonstration, farmer to farmer visits, leaflets and pamphlets, audiovisuals etc. In Khulna district dissemination and extension services are application of government rules and regulations, strategic management, pond/shrimp farm visit, public awareness, training facilities, financial and other supports and some research projects also applied, training program, the number of trained fish farmers and trained shrimp farmers in 2009 were 790 and 5,754 respectively. In Satkhira district, different extension programs are applied, such as shrimp demonstration, fish sanctuary, pond/shrimp farm visit, training program, the number of trained Fish farmers and trained shrimp farmers in 2009 were 934 and 2110 respectively and community based fisheries management and some research projects. In Jhenaidah district DoF activities are training, in sadar upazila number of trained fisherman 34, baor management, identify floodplain and other involved communities, awareness campaign, frame survey, arrangement of fund, credit facilities, training program, production monitoring, identification of disadvantaged groups and pollution, disease diagnostic and its control. Keywords: Training farmers; Extension; Visits; Demonstration DOI: 10.3329/jbau.v8i2.7947 J. Bangladesh Agril. Univ. 8(2): 341-346, 2010